Sexual and ontogenetic morphometric variation in Xiphopenaeus kroyeri (Crustacea, Decapoda, Penaeidae): a new approach with linear and angular morphometric data. Issue 3 (3rd July 2018) - Moraes, S. A. S. N.; Alencar, C. E. R. D.; Fransozo, A.; Costa, R. C.; Castilho, A. L.; Freire, F. A. M.
Abstract: The present study evaluates the ontogenetic/sexual morphometric variation in Xiphopenaeus kroyeri . Sampling was from July 2001 to June 2003 at Ubatuba, São Paulo, Brazil. Animals were sexed and measured (cephalothorax length-CC, partial of the rostral spine-CPR, rostral spine-CR and rostral spine angulation-AR). Data analysis included linear morphometric analysis: equation ln y = ln a + ln b (sex/ontogeny fitting), k-means method (ontogenetic classification), analysis of covariance (morphological maturity), removal of the allometric effect, verification of parametricity and collinearity, principal component (PCA) and linear discriminant analysis (visualization of tendencies), permutational multivariate analysis of variance (hypothesis test). In addition, circular analysis was undertaken: circular normal distribution and concentration parameter, circular analysis of variance (hypothesis test), PCA (observe tendencies) and linear-circular regression (ontogenetic trajectory, RA-dependent variable, CL-independent variable). Morphological changes in the cephalothorax, in the adult stage, may be related to the increase in size of the gonads during sexual maturation and to the development of gills during the transition from arthrobranch (juvenile) to dendrobranch (adult). The rostral spine, in the adult stage, tends to become more elongated and more sharply angled. This feature may be related to predation pressure on larger specimens (adults), knowing that throughout its ontogeny the rostral spine of this species assumes phenotypic traits that make swallowing more difficult for predators.